Implementasi Pengkondisian Kipas dan Lampu Otomatis Menggunakan Logika Fuzzy - Randy Maulana; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Electrical energy needs in Indonesia is increasing along with economic growth and national industry and population growth every year. This increase occurs because electronic appliances such as air conditioners are left on, even though no one is in the room, the same example on the TV and left lit continuously in a room. This common practice is due to the principle of electronic devices using the on-off principle. To overcome these problems in this study will implement a system of fan and lamp conditioning using Fuzzy logic. The system will use some hardware such as Arduino Mega microcontroller with LDR input sensor as light sensor, DHT11 as temperature sensor, and two ultrasonic sensors as motion and distance sensors, and output will use DC motor as fan, and LED as lamp. Fuzzy logic on the system will use the help of Embedded Fuzzy Logic Library (eFLL), the library is used to facilitate the implementation of fuzzification process that determines the membership function of input and output, the inference process is the formation of Fuzzy rules and defuzzification process that is convert the input value into firm value. The level of accuracy and success of Fuzzy logic on the system will be tested by comparing the value of system output on the tool with the system output value in MATLAB. The average accuracy obtained for fan output reached 98.77% and the lamp output reached 92.54%.